Chiral Lead‐Free Hybrid Perovskites for Self‐Powered Circularly Polarized Light Detection - Li, Dong; Liu, Xitao; Wu, Wentao; Peng, Yu; Zhao, Sangen; Li, Lina; Hong, Maochun; Luo, Junhua (Angewandte Chemie International Edition, 2021)
Metal‐halide perovskites are recently emerging as the promising alternative for CPL detection owing to their CPL‐sensitive property induced by chiral organics and efficient charge transport of inorganic frameworks. However, most of these reported chiral perovskites involve high concentrations of toxic Pb which will become the potential bottleneck for their further application. Herein, we successfully developed two lead‐free halide double perovskites, [(R)‐β‐MPA]4AgBiI8 ((R)‐β‐MPA=(R)‐(+)‐β‐methylphenethylammonium, 1‐R), and [(S)‐β‐MPA]4AgBiI8 ((S)‐β‐MPA=(S)‐(−)‐β‐methylphenethylammonium, 1‐S). Circular dichroism measurements reveal that these perovskites exhibit notable chirality induced by organic cations to distinguish different polarization states of CPL photons. Significantly, they present unique chiral polar photovoltaic, and resulting self‐powered CPL detection without an external power source is unprecedentedly achieved. Furthermore, an anisotropy factor up to 0.3 is acquired for the self‐powered CPL detection, reaching the highest value among reported chiral perovskites. This work suggests hybrid double perovskites are promising photoelectronic candidates, and provides a new approach for exploring new “green” circularly polarized light‐sensitive materials with high performance. Chiral lead‐free double hybrid perovskites are successfully acquired by assembling chiral organic cation with Ag+ and Bi3+ double metals. Benefitting from chiral polar bulk photovoltaic effects induced by polar structure, self‐powered circularly polarized light detection with a high anisotropy factor of 0.3 is unprecedentedly achieved in chiral hybrid perovskites.